CONTRIBUTION OF AGRICULTURAL SECTOR AND ITS REFLECTION ON GDP IN INDIA - Theenathayalan, S.; Murugan, S. (International Journal of Psychosocial Rehabilitation, 2024)
This paper aims to analyse the relationship between the contribution of agriculturalsector and the total GDP in India. Agricultural sectorin India is expected to generatebetter momentum in next few years due to increased investment in agriculturalinfrastructure. Increased agricultural output and productivity tend to contributesubstantially to the overall economic prosperity of a nation which is predominantlyagricultural and over-populated. Still agriculture in India is the backbone of the countryand is regarded as the largest sector of the country’s economic activity. The regressionresult shows that one percent increase in agricultural GDP which leads to increases 1.79per cent of total GDP. The R2 value is 0.95. It shows the present contributory position ofIndian Agricultural sector. Above the all without Agricultural and Allied Activities noone can survive in the earth. In this relation Agricultural GDP has positive impact on notonly in India’s GDP but also for the people who involved in industrial and service sectoractivities.